The Concept of Therapeutic Justice as a Model of Formal Social Reaction to Crime - Bulatović, Aleksandra; Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Institutional reaction to crime is based on formal norms and their implementation. Therapeutic jurisprudence alters the traditional perspective on crime as it is outlined by criminal procedure. The new perspective is founded on an analysis of interactions between actors in proceedings and the consequences of those proceedings. Law is understood as a regulator of social relations that supports their advancement. At the centre of the concept of therapeutic jurisprudence, the consequences of the application of legal norms are situated, as they are directed towards emotions and the psychological dimension of the legal system's functioning. In the article, authors highlight therapeutic jurisprudence's capacity to influence convergence of subjective and objective well–being as a result of optimisation of social relations within a wider framework set by social values. The aim of this article is to point towards the perspective of implementation of therapeutic justice to intensify a quest for better ways and approaches to confronting problems in a way that is more appropriate than that of traditional criminal procedure.